Efektivitas Perma Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan dalam Menekan Angka Cerai di Pengadilan Agama - Andaryuni, Lilik; Haika, Ratu (FENOMENA, 2018)
Raising statistic divorce from year to year increased, make Supreme Court take various efforts, among others make the role of mediation in the Religious Court (PERMA No. 1 Tahun 2016). This article discusses the effectiveness of mediation in the Religious Court in order to minimize statistic divorce in the Religious Court East Kalimantan.